Stearoyl-coenzyme A desaturase 1 is required for lipid droplet formation in pig embryo. Issue 3 (March 2019) - Lee, Dong-Kyung; Choi, Kwang-Hwan; Hwang, Jae Yeon; Oh, Jong-Nam; Kim, Seung-Hun; Lee, Chang-Kyu
Abstract : Lipid droplets (LD) provide a source of energy, and their importance during embryogenesis has been increasingly recognized. In particular, pig embryos have larger amounts of intercellular lipid bilayers than other mammalian species, suggesting that porcine embryos are more dependent on lipid metabolic pathways. The objective of the present study was to detect the effect of stearoyl-coenzyme A desaturase 1 (SCD1) on LD formation and to associate these effects with the mRNA abundance of LD formation-related genes ( SREBP, ARF1, COPG2, PLD1 and ERK2 ) in in vitro -produced porcine embryos. To determine the effect of SCD1 on LD formation and related genes, we examined the effects of SCD1 inhibition using CAY10566 (an SCD1 inhibitor, 50 μM) on parthenogenetic embryos. SCD1 inhibition downregulated the mRNA levels of LD formation-related genes and embryo development. Our results revealed that SCD1 functions in the regulation of LD formation via phospholipid formation and embryo development. In addition, we treated parthenogenetic embryos with oleic acid (100 μM), which led to a significant increase in the blastocyst formation rate, LD size and number compared to controls. Remarkably, the adverse effects of the SCD1 inhibitor could be counteracted by oleic acid. These data suggest that porcine embryos can use exogenous oleic acid as a metabolic energy source.